A seu tempo : um estudo sobre transições familiares precoces em Portugal no contexto Europeu - Carvalho, Diana (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2016)
This paper critically explores the narratives associated with transitions to adulthood and focuses on the earliest occurrences of the private sphere transitions in Portugal. Using data from the European Social Survey (2006), the conclusion is that life course competing perspectives coexist. Survival analysis allows testing the significant effect of generations, although a steady trend towards greater postponement is not observed. Regressions reveal that girls are associated with earlier family transitions and educational background is only significant for the younger generation.